University Students’ Awareness of the Role of Culture in the Language Learning Process - Abdullah, Nian (Humanities Journal of University of Zakho, 2024)
To learn English language and communicate in different contexts successfully, English language students need to learn about the culture of English native speakers in spite of mastering the linguistic knowledge of the language. Indeed, culture shapes the language just as it shapes the life of its speakers. However, it is unknown whether students are aware of the role of culture in the language learning process and in case they are aware, it is still not evident how they learn about the culture. To learn about these two aspects, the current study explores undergraduate students’ awareness in this regard. It uses a four-Likert scale questionnaire to elicit answers from 45 EFL junior students in English Department. The results demonstrated that the majority of students are aware of the role of culture on English language learning and they use different methods to learn about the culture. Their awareness can be exploited to make culture part of English language teaching programs at universities.